2022
DOI: 10.1088/1742-6596/2224/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Approaches in Health Care Sector to The Diagnosis of Breast Cancer

Abstract: Breast cancer (BC) is a kind of malignant disease that represents the primary reason of women’s death around the world, cancer cells form tumors which lead to weakening the functioning of the immune system. If the main risk factors are known and detected correctly, the cure rate becomes higher, and the inappropriate treatments which are the main cause of death will be avoided. Today, several avenues for advancing breast cancer classification research are being studied, in particular to strengthen screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…They observed that a 96.1% accuracy could be attained using the decision tree approach. Six data mining methods for detecting breast cancer were evaluated by Wassim et al [27]. Decision trees, naive Bayes classifiers, support vector machines, random forests, k-nearest neighbors, and neural networks were some of the algorithms employed.…”
Section: Related Workmentioning
confidence: 99%
“…They observed that a 96.1% accuracy could be attained using the decision tree approach. Six data mining methods for detecting breast cancer were evaluated by Wassim et al [27]. Decision trees, naive Bayes classifiers, support vector machines, random forests, k-nearest neighbors, and neural networks were some of the algorithms employed.…”
Section: Related Workmentioning
confidence: 99%
“…Research on Badr and Abou uses python with genetic algorithm and cuckoo search algorithm with 84% accuracy [8] [16]. Wassim's research uses a rapidminer with the K Nearest Neighbors (K-NN) algorithm, Naive Bayes (NB), and the Support Vector Machine (SVM) with the best accuracy owned by SVM with a size of 97.07% [17].…”
Section: Introductionmentioning
confidence: 99%